(untitled) (TAJ: Journal of Teachers Association, 2010)
With the advancement of endourology, ureteric stones are mostly managed by intracorporeal lithotripsy via ureteroscopes, or by extracorporeal lithotripsy. Placement of ureteric stent is almost a routine after ureteric stone lithotripsy. Though stenting is necessary to prevent some post-operative complications, especially in difficult and complicated lithotripsy, it is associated with some morbidity as well. This study was carried out to compare the complications of the patients with or without stenting after uncomplicated ureteroscopic removal of ureteric stones. 50 patients with ureteric stone, amenable to ureteroscopic management, were prospectively randomized into a stented (25) and an unstented (25) group. 9.5 or 8.5Fr ureteroscope was used for the procedures. Pneumatic lithotripter was used for stone fragmentation and stone / fragments were removed by grasper or by dormia basket. Symptom questionnaires were completed by asking the patients after the procedures regarding the complication of flank pain, urinary symptoms and haematuria. In this study, there was no statistically significant difference in age, stone size, or hospital stay between the groups (p>0.05). Haematuria was more in stented than that of unstented group (p=0.001). Flank pain and dysuria occur in both the groups without any significant difference. Frequency of micturation and lower abdominal pain developed more commonly in stented than that of unstented group. Operative duration is more in stented than that of unstented group but not significant statistically. So, in our opinion, routine use of ureteric stent after uncomplicated ureteroscopic removal of ureteric stone is not necessary. TAJ 2010; 23(1): 38-40